The Polystyrene fibers recycled waste produced by Solution Blow spinning with TiO2 incorporation - Padovani, Guilherme S; Carvalho, Samuel A. P. T.; de Paula, F. R. (International Journal of Scientific Research and Management (IJSRM), 2021)
This study attempted to produce polymeric microfibers with low-cost and photocatalytic properties, making it possible to remedy two modern problems, plastic disposal and irregular effluent disposal, for which we used the solution blows pinning (SBS) technique to produce recycled polystyrene (PS) microfibers (recycled waste from transparent barrel pen), the use of the SBS also has good mobility for the benefit of fibers, allowing the fibers to be produced directly under the surface where intend to be used, through the SEM was found the ideal concentration to produce uniform microfibers. With the minor average diameter, FTIR analysis of the fibers showed peak characteristics of PS, demonstrating that most of the transparent barrel pen is composed of PS. The as-prepared fibers of recycled PS were incorporated into their polymer solution with a TiO2 Degussa P25 concentration of 10% (w/w) concerning the polymer mass. For the study of photocatalytic activity, the dye Rhodamine B was used as an indicator. Excellent photocatalytic activity, XRD pattern of PS and PS/TiO2-10% fibers showed PS and TiO2 in two phases, anatase and rutile.